Avaliação da prática do acolhimento às crianças de zero a seis anos em Unidades de Saúde da Família - Liliane da Consolacao Campos Ribeiro (2012)
A integrative revision was carried through that objectified to search and to evaluate evidences in literature concerning the reception of health of the family. The bibliographical survey enclosed national and international publications, in the Virtual Library in Health, being identified 42 national references. The results had pointed divergences between the concepts presented for the authors on the shelter and the care practical of the units of health of the family. Thus the identification of efforts for the development becomes necessary to produce other research and to maximize the assistance of the professionals in the Family HealthStratgy , in order to make possible the integration of theory and practice.